COMBINING ABILITY AND HETEROSIS STUDIES FOR SELECTING ELITE PARENTS AND HYBRIDS IN RICE ( ARENTS AND HYBRIDS IN RICE (Oryza SATIVAL.) - MANJUNATH KENCHARAHUT,; Y. CHANDRA MOHAN,; V. GOURI SHANKAR,; M. BALRAM,; L. KRISHNA, (The Bioscan, 2019)
Combining ability and heterosis studies in rice with a set of 32 hybrids along with their parents (B and R lines) and standard checks viz., MTU 1010 and US 314 were evaluated for grain yield and related traits.The mean performance of the hybrids for most of the characters was higher than that of parents. The analysis of variance revealed significant differences among parents, lines and hybrids for most of the characters studied. Degree of dominance was more than unity for all the traits except for days to 50% flowering (0.72) plant height (0.68) and number of grains per panicle (0.68). SCA variances were higher than GCA variances for most of the characters, which indicated the predominance of non-additive gene action. The gca effects revealed that among the lines IET- 19321 had significant gca effects in desired direction for several traits including yield. Among the testers, CMS 59A was a good general combiner. Among thirty two hybrids, CMS 59A x TP 30433, CMS 23A x TP 30433 and JMS13 x WGL 823 were found good specific combiners. Seventeen hybrids were recorded positive significant standard heterosis over variety (MTU 1010), whereas eight hybrids were recorded positive significant heterosis over hybrid check (US 314). Overall data revealed that CMS 23A x JGL 20649, JMS 13A x JGL 5614, CMS 64A x WGL 823, CMS 64A x IET 19321 and JMS 13A x WGL 823 were identified as potential hybrids with respect to all characters based on their sca and heterosis estimates.